Reward System, Employee Engagement, and the Role of Employee Satisfaction as Mediating Variable - Yushe Marleyna; Devie Devie; Foedjiawati Foedjiawati (Master of Management, School of Business and Management, Petra Christian University, 2022)
A good reward system is believed to be a determinant in achieving organizational goals. When employees are satisfied with the applied reward system, employee engagement will manifest, which can encourage the achievement of organizational goals. This study aims to determine the correlation between the reward system and employee engagement mediated by employee satisfaction at PT. X, a company engaged in the property sector. The research is based on a survey collected from 41 employees working at PT. X. Data analysis was carried out using the PLS-SEM model suitability test technique with SmartPLS 3. The results of data analysis show that employee satisfaction partially mediates the correlation between the reward system and employee engagement (T-statistics 2.257, p-values 0.024).